Control measures to reduce Salmonella spp. and L. monocytogenes contamination in mung bean seeds and managing their growth during sprouting - Lee, Ha Kyoung; Yoon, Ki Sun (Food Science and Preservation, 2024)
Abstract Contaminated seeds pose a significant risk for foodborne disease related to sprouts. We investigated to assess the effect of various control measures (ultraviolet-C light-emitting diodes, UVC LED; slightly acidic electrolyzed water, SAEW; UVC waterproof-LED, UVC W-LED, and 60°C mild heat), both individually and in combination, on mung bean seeds to mitigate the growth of Salmonella spp. and L. monocytogenes during germination. Mung bean seeds inoculated with Salmonella spp. and L. monocytogenes were germinated in sprouting equipment at 25°C with 85% relative humidity for 4 days. No significant effects (p<0.05) on germination rate or total aerobic bacterial growth in mung bean sprouts were observed with individual treatments. However, combined treatments significantly (p<0.05) inhibited pathogen growth during germination compared to the control (no treatment) and were particularly effective in mung bean sprouts contaminated with L. monocytogenes. Treating seeds with SAEW+mild heat or UVC W-LED achieved the highest reduction of both pathogens in seeds and resulted in the least growth of both pathogens in sprouts among the tested treatments. Since UVC W-LED demonstrated efficacy in preventing cross-contamination of washing water, combined treatments of SAEW with UVC W-LED or mild heat identified as economically viable options for ensuring the production of safe sprouts in the sprout industry.